Nitrogen partitioning and dry matter distribution in three cowpea cultivars. - Silveira, Joaquim A. G. da; Castro, Paulo R. C.; Dechen, Antonio R. (Pesquisa Agropecuaria Brasileira, 2014)
The N - mobilization intensity from vegetative organs into growing seeds is a determinative factor on yield of legume crops. With the objective of studying this relationship, an experiment was carried out in pots, under natural conditions, using three cowpea (Vigna unguiculata (L) Walp.) cultivars with distinct yield potentials for production under tillage conditions: Epace-1 (1,600 kg.ha-1) and Epace (1,200 kg.ha-1) and Epace-8 (1,300 kg.ha-1). The plants were harvested 14, 28, 42, 56, and 70 day after germination (DAG). The N accumulation, expressed by g.plant-1 days showed a positive relationship with dry matter (DM) production. At 70 DAG, Epace-6 and Epace-8 cultivars presented 57 % and 53%, respectively of total plant N into seeds plus pods, while Epace- 1 cultivar yielded 14% only. During the seed-filling period (56 to 70 DAG) of the more precocious cultivars (Epace-6 and Epace-8) a pronounced decrease occurred in relative N content of leaves (64% and 58%), stems (65% and 61%) and roots (32% and 36%), respectively. Epace-1, later cultivar, presented 30% and 8% decrease in leaves and roots, respectively, and an 8% increase in stems for the same time interval. It is possible that the difference in yield among the three cultivars be associated with duration of the period of N mobilization from vegetative organs.